Economics of farm management in a global setting - Olson, Kent D. (Hoboken, N.J. : Wiley, 2010)
'Farm managers will appreciate this book as they learn the principles of farm management; from the basics of management and economics; to the details of strategy and operations. It presents economic concepts, such as the discussion of markets, competitive forces, and macroeconomics, which is new to farm management texts. Material is included on strategy, marketing, budgeting, production and operations, quality, finance, investment, risk, contracts, staffing, business organisation, farm succession, and the future. Strategic management and quality management as well as new techniques and tools in production and operations management are also examined. This approach will help farm managers improve the efficiency, effectiveness, objectivity, and, ultimately, success of their decisions'--
Machine generated contents note: 1. Managing the Farm in an Integrated World Economy -- 2. Management -- 3. Business Plans -- 4. Lessons from Microeconomics -- 5. Lessons from Macroeconomics -- 6. Government Policies Affecting Farming around the World -- 7. Strategic Management: Planning -- 8. Strategic Management: External and Internal Analysis -- 9. Crafting Strategy -- 10. Strategy Execution and Control -- 11. Marketing Basics -- 12. Financial Statements: Balance Sheet, Income Statement, Statement of Owner's Equity, and Statement of Cash Flows -- 13. Financial Analysis -- 14. Financial Management -- 15. Enterprise Budgets: Uses and Development -- 16. Partial Budgets -- 17. Whole-Farm Planning -- 18. Operations Management for the Farm -- 19. Quality Management and Control -- 20. Investment Analysis -- 21. Land Ownership and Use -- 22. Risk Management -- 23. Production Contract Evaluation -- 24. Human Resource Management -- 25. Business Organization -- 26. Farm Transfer and Succession Planning -- 27. Farming in the Future.
Includes bibliographical references and index.
Keywords: Farm management; Agriculture -- Economic aspects; BUSINESS & ECONOMICS / Development / Economic Development